1975
DOI: 10.1042/bj1500373
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative phosphorylation during glycollate metabolism in mitochondria from phototrophic Euglena gracilis

Abstract: Mitochondria were isolated by gradient centrifugation on linear sucrose gradients from broken cell suspensions of phototrophically grown Euglena gracilis. An antimycin A-sensitive but rotenone-insensitive glycollate-dependent oxygen uptake was demonstrated in isolated mitochondria. The partial reactions of glycollate-cytochrome c oxidoreductase and cytochrome c oxidase were demonstrated by using Euglena cytochrome c as exogenous electron acceptor/donor. Isolated mitochondria contain glycollate dehydrogenase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Bird et al (2,3) using Nicotiana tabacum leaf mitochondria, and Collins et al (7) using Euglena gracilis mitochondria, reported that the reaction required aerobic conditions, was linked to the electron transport chain, and coupled to the synthesis of 2 (2) or 1 (7) molecule of ATP for each molecule of serine formed. In agreement with Bird et al (2,3) and Collins et al (7) it is clear from Figure 4 that the oxidation of glycine is linked to the mitochondrial electron transport chain, and is sensitive to electron transport and phosphorylation inhibitors. However, in contrast to Bird et al (2,3) and Collins et al (7), we found that the glycine oxidation is coupled to three phosphorylation sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bird et al (2,3) using Nicotiana tabacum leaf mitochondria, and Collins et al (7) using Euglena gracilis mitochondria, reported that the reaction required aerobic conditions, was linked to the electron transport chain, and coupled to the synthesis of 2 (2) or 1 (7) molecule of ATP for each molecule of serine formed. In agreement with Bird et al (2,3) and Collins et al (7) it is clear from Figure 4 that the oxidation of glycine is linked to the mitochondrial electron transport chain, and is sensitive to electron transport and phosphorylation inhibitors. However, in contrast to Bird et al (2,3) and Collins et al (7), we found that the glycine oxidation is coupled to three phosphorylation sites.…”
Section: Discussionmentioning
confidence: 99%
“…For electron microscopy, mitochondria in suspending medium (0.3 M mannitol, 10 mm MOPS buffer [pH 7.4]) were fixed for 1 hr in 3% glutaraldehyde. After centrifugation, the pellet was washed twice with suspending medium and was postfixed with 1 % OsO dissolved in suspending medium.…”
Section: Methodsmentioning
confidence: 99%
“…In unicellular algae, D-lactate can be oxidized slowly by a dehydrogenase, which has generally been named glycolate dehydrogenase (18), and is associated with the mitochondrial membrane (1). The electron acceptor or cofactors for this dehydrogenase are unknown, but there is some evidence that it is coupled to the mitochondrial electron transport system (3,20). An enzyme activity which reduces pyruvate has been reported for various green algae (10,12,14,24) and in this paper its partial purification and characterization are further reported.…”
mentioning
confidence: 99%
“…It was further noted from this experiment that ['4C]glycolate accumulated during photosynthesis with NaH14C03 in the presence of SHAM in dk97 cells ( (4,5). However, the direct electron acceptor for both the algal glycolate and D-lactate dehydrogenase activities is still unknown.…”
Section: Resultsmentioning
confidence: 98%
“…In unicellular algae, however, oxidation of glycolate is catalyzed by a mitochondrial membrane-bound glycolate dehydrogenase (1)(2)(3)(4)(5). Glycolate-dependent reduction of cytochrome c by Chlamydomonas (6) and glycolate-dependent 02 uptake by mitochondria prepared from Euglena gracilis (4,5) have been reported. Glycolate dehydrogenase does not directly transfer electrons to oxygen; however, the natural acceptor is unknown (1).…”
mentioning
confidence: 99%